Rapid Contamination Detection in Validamycin A Production by HS-SPME/GC-MS - Yu, Xiao-Mei; Jiang, Jing; Yang, Shang-Tian; Zhou, Wen-Wen (Current Biochemical Engineering (Discontinued), 2020)
Background: Validamycin A (Val-A) is one of the most widely used agricultural antibiotics in East Asia especially for controlling rice sheath blight disease. Fermentation contamination of the industrial Val-A producing strain is a common occurrence. Methods: Fermentation culture of S. hygroscopicus 5008 has a special smell that could be distinguished from other tainted samples. The change of the volatiles in untainted and tainted samples was characterized using headspace solid phase microextraction (HS-SPME) combined with gas chromatography- mass spectrometry (GC-MS). Results: Seventy-one volatile compounds (including alkanes, amines, alcohols, esters, aldehydes and others) were identified and there were significant differences in the composition of volatiles among different samples. Principal component analysis (PCA) based on the GC-MS data was used to identify the important volatile compounds that contributed to the differentiation of the fermentation samples under different fermentation stages, as well as among different pollution species and fermentation media. Contamination could be discovered in time irrespective of the stage of fermentation and the contaminating bacteria in broth. Conclusion: It is the first report to detect contamination by volatile compounds in the antibiotic fermentation and it was proved that HS-SPME/GC-MS is an effective contamination detection method in Val-A production.
Keywords: GC-MS